STRATEGI KOMUNIKASI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DALAM MENSOSIALISASIKAN PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) DI KOTA PEKANBARU - Wia Ruri Wilanda; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In accordance of law No. 40 of 2004 on National Social Security Systems (SJSN) to provide comprehensive social security for everyone in order to meet the basic needs of a decent living towards the realization of a prosperous Indonesia society, fair, and prosperous. In Act No. 36 of 2009 on health also asserted that everyone has equal rights to obtain access to resources in the areas of health and obtain health services that are safe, high quality, and affordable. Of the Act, without exception all communities in mandatory Inonesia became participants of the BPJS. Health coverage is universally expected to be started gradually in 2014 and 2019, expected throughout Indonesia citizens already have health coverage. As for the purpose of this research is to find out and analyze the strategies of health city of Pekanbaru BPJS communicators in disseminating national health assurance program (JKN) in the city of Pekanbaru and to know the strategies of health city of Pekanbaru BPJS audiences in disseminating national health assurance program (JKN) in the city of Pekanbaru.This research was conducted in the city of Pekanbaru Health BPJS. The subject of this research is in the field of employee Guidance on Health BPJS Pekanbaru that add up to 10 people as informant (head of the branch, the head of the Unit's marketing, and staff) and the community that's been incorporated and is not incorporated as a participant BPJS health. In accordance with the research objectives that have been mentioned above, then the required data, among other data of primary and secondary data. Data collection techniques to do with interview techniques, observation and the study of librarianship. A data analysis method used in this research is descriptive qualitative analysis method of. The results showed that the BPJS Health communication strategy in disseminating national health assurance program (JKN) includes strategies of health city of Pekanbaru BPJS communicators, Health strategy audiences BPJS Pekanbaru, message strategy Health BPJS Pekanbaru, and media strategies of health city of Pekanbaru BPJS.Keywords: strategy, Communications JKN Progam Socialization